2009
DOI: 10.1128/mcb.00857-08
|View full text |Cite
|
Sign up to set email alerts
|

Tropomyosin Isoform Expression Regulates the Transition of Adhesions To Determine Cell Speed and Direction

Abstract: The balance of transition between distinct adhesion types contributes to the regulation of mesenchymal cell migration, and the characteristic association of adhesions with actin filaments led us to question the role of actin filament-associating proteins in the transition between adhesive states. Tropomyosin isoform association with actin filaments imparts distinct filament structures, and we have thus investigated the role for tropomyosins in determining the formation of distinct adhesion structures. Using co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
109
1
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 69 publications
(119 citation statements)
references
References 46 publications
(72 reference statements)
8
109
1
1
Order By: Relevance
“…In contrast, B35 cells stably overexpressing B5-fold higher levels of Tm5NM1 (B35.Tm5NM1) (Figure 1b) were predominantly elliptical with numerous short, pericellular protrusions ( Figure 1c). Agreeing with our earlier report that Tm5NM1 reduces migration speed of cells in 2D culture systems (Bach et al, 2009), Tm5NM1 overexpression significantly reduces migration speed within 3D collagen gels (Figure 1d). Indeed, B35.Tm5NM1 cells within 3D matrices are fundamentally stationary (speeds o0.05 mm/min represent cell oscillation rather than actual cell migration), and we observe very little translocation of cell bodies in these cultures.…”
Section: Tm5nm1 Inhibits Mesenchymal Migrationsupporting
confidence: 90%
See 4 more Smart Citations
“…In contrast, B35 cells stably overexpressing B5-fold higher levels of Tm5NM1 (B35.Tm5NM1) (Figure 1b) were predominantly elliptical with numerous short, pericellular protrusions ( Figure 1c). Agreeing with our earlier report that Tm5NM1 reduces migration speed of cells in 2D culture systems (Bach et al, 2009), Tm5NM1 overexpression significantly reduces migration speed within 3D collagen gels (Figure 1d). Indeed, B35.Tm5NM1 cells within 3D matrices are fundamentally stationary (speeds o0.05 mm/min represent cell oscillation rather than actual cell migration), and we observe very little translocation of cell bodies in these cultures.…”
Section: Tm5nm1 Inhibits Mesenchymal Migrationsupporting
confidence: 90%
“…Importantly, expression of this isoform can vary up to 5-fold between different tissues, with the highest levels observed in lung tissue . Furthermore, we have previously demonstrated that Tm5NM1-mediated stabilization of the actin filaments causes significant inhibition of focal adhesion disassembly (Bach et al, 2009). Given that focal adhesion turnover is required for mesenchymal migration, these results suggested that Tm5NM1 might specifically block mesenchymal migration.…”
Section: Introductionmentioning
confidence: 88%
See 3 more Smart Citations